The Psychological Impact of Coronavirus Disease 2019 on Nurses in Saudi Arabia and Their Coping Strategies - Al Muharraq, Essa H. (SAGE Open Nurs, 2021)
AIMS AND OBJECTIVES: To explore the psychological impact of coronavirus disease 2019 on frontline nurses working in Jazan, Saudi Arabia, and their coping strategies. BACKGROUND: As the coronavirus disease 2019 pandemic continues to expand globally, healthcare systems have become more overwhelmed than ever before, placing a great psychological strain on frontline nurses. DESIGN: A cross-sectional, observational, quantitative study. METHODS: In total, 215 frontline nurses working at 12 hospitals across Jazan, Saudi Arabia, were recruited. Data were collected during August 2020 using a modified version of the severe acute respiratory syndrome team questionnaire. RESULTS: Roughly two-thirds (62.3%) of the participants reported moderate to high levels of nervousness and fear at work. Ethical and moral responsibility has been determined as the main motivator for frontline nurses to practice their profession, with 88% of them expressing a willingness to work even if the situation deteriorated further. However, 87% of the participants were extremely concerned about transmitting the disease to their family members. The most common coping strategy adopted by the nurses appeared to be adherence to strict protective measures (93.5%), followed by the acquisition of more knowledge about the disease (82.3%). CONCLUSION: Frontline nurses experience severe psychological stress, which is mainly caused by their fear of contracting the infection or passing it on to their family members. Thus, proper education, adherence to infection control protocols, effective social support system, and access to sufficient personal protective equipment will help nurses enhance their coping abilities.